THE IMPORTANCE OF USING INNOVATIVE TECHNOLOGIES IN TEACHING THE EPIC OF ALPOMISH (European Science Methodical Journal, 2024)
This article deals with modern methods of teaching Uzbek folk epics today and views and reflections on the effectiveness of innovative methods in teaching Uzbek folk epics, including the Alpomish epic. At the same time, the importance of innovative methods in the outcome of the lesson and the development of creative abilities of students is revealed.